Analysis Determination Open Unemployment in Cities/Regencies East Java Province - Arifin, Muchammad Yudha; Khusaini, Mohamad; Wahyudi, Setyo Tri (Journal of International Conference Proceedings, 2023)
This study aims to analyze variables that affect the open unemployment rate in East Java Province for the period 2017 – 2022, including Economic Growth, Inflation, Wage Rate, and Education. This research uses quantitative methods with data collection methods from a number of publications of related agencies, namely BPS East Java Province. The specification that the data used in this study is panel data for the period 2017 – 2022 with details of the number of observations as many as 5 cities/regencies in East Java Province. The results of this study show that simultaneously Economic Growth, Inflation, Wage Rate and Education have an influence on Open Unemployment. However, partially the variables Inflation and Education do not have an influence on the variable Unemployment, while Economic Growth and Wage Rate have an influence on the variable unemployment. The results of this study show that to reduce the open unemployment rate can be done by increasing the rate of economic growth, consistently increasing the wage level